An instantaneous discharging liquid-solid triboelectric nanogenerator (IDLS-TENG) with boosted peak power output. (August 2021) - Xu, Wei; Yang, Jiayi; Liu, Shuangshuang; Meng, Yan; Feng, Di; Jia, Lingjie; Liu, Sida; Wang, Baolong; Li, Xiuhan
Abstract: Liquid-solid triboelectric nanogenerator (LS-TENG) has emerged as a powerful tool in energy harvesting and motion detecting. There is a recognized need for improving the power output and signal-to-noise ratio of LS-TENG. The instantaneous discharging mechanism of LS-TENG is studied and experimentally realized by a controllable switch structure in this paper. The peak short circuit current and peak power output (at 1 MΩ) are increased by over 26 and 1700 times, respectively, with respect to the control LS-TENG working in the single electrode mode. This research provides a fresh insight in designing sensors with high signal-to-noise ratio and energy harvestors that have a superior performance in driving devices with low load resistance. Graphical Abstract: Liquid-solid triboelectric nanogenerator (LS-TENG) has emerged as a powerful tool in energy harvesting and motion detecting. There is a recognized need for improving the power output and signal-to-noise ratio of LS-TENG. The instantaneous discharging mechanism of LS-TENG is studied and experimentally realized by a controllable switch structure in this paper. The peak short circuit current and peak power output (at 1 MΩ) are increased by over 26 and 1700 times, respectively, with respect to the control LS-TENG working in the single electrode mode. This research provides a fresh insight in designing sensors with high signal-to-noise ratio and energy harvestors that have a superior performance in driving devices with low load resistance. ga1 Highlights: Enhanced short circuit current output compared to LS-TENG working in single electrode mode is obtained. Greatly enhanced peak power output especially with low load resistance is obtained. The proposed IDLS-TENG has a great application potential in self-powered sensors with high signal-to-noise ratio.